2011
DOI: 10.1177/0040517511407373
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of alkyl-dimethyl-benzyl-ammonium chloride on differently pretreated non-woven cotton substrates

Abstract: The adsorption of alkyl-dimethyl-benzyl-ammonium chloride (ADBAC), a cationic surfactant commonly employed as an antimicrobial agent, on greige, alkaline scoured, and bleached non-woven cotton fabrics was investigated at varying surfactant concentrations using ultraviolet-visible spectroscopy. Results show greige cotton non-wovens adsorb roughly three times the ADBAC in aqueous solution than bleached cotton and 1.5 times more than scoured cotton non-wovens. At a constant ADBAC concentration of 0.625 g/l, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…In Region I, surfactant molecules adsorbed as individual ions, and the adsorption was driven via electrostatic interactions between the surfactant head groups and the carboxylic sites on the negatively charged cotton surface. Previous research 29,30 has shown that the presence of pectin and waxes in untreated raw cotton greatly increases the adsorption of cationic surfactants via electrostatic and hydrophobic interactions, respectively. Due to the resulting high q e , raw cotton showed only Region II at the concentration range of ADBAC studied, and its Region I is expected to lie in lower concentrations.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…In Region I, surfactant molecules adsorbed as individual ions, and the adsorption was driven via electrostatic interactions between the surfactant head groups and the carboxylic sites on the negatively charged cotton surface. Previous research 29,30 has shown that the presence of pectin and waxes in untreated raw cotton greatly increases the adsorption of cationic surfactants via electrostatic and hydrophobic interactions, respectively. Due to the resulting high q e , raw cotton showed only Region II at the concentration range of ADBAC studied, and its Region I is expected to lie in lower concentrations.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…4,5 Previous research has shown that both the rate and total amount of biocide adsorbed from a bulk solution was significantly greater for greige cotton than scoured and bleached cotton nonwovens. 6 It is expected that these previous results are applicable to all greige cotton containing materials, regardless of form. Greige cotton is not naturally wettable to water due to waxes on the surface of the fiber; however, in the presence of surfactant, greige cotton will wet out.…”
Section: Introductionmentioning
confidence: 71%
“…In a previous investigation of the adsorption of ADBAC on differently pretreated nonwoven cotton substrates, the greige substrates were found to have adsorbed three times more ADBAC at a faster rate than scoured and bleached substrates. 6 Cationic surfactants, like ADBAC, mainly adsorb onto cotton substrates via hydrophobic and electrostatic interactions. It is well known that cotton exhibits a negative electric surface charge when immersed in neutral aqueous solutions; 8 thus, it was expected that the nonwoven substrates in the previous study would adsorb the positively charged ADBAC molecules from the bulk cationic surfactant solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of ADBAC depleted from the bulk solution by absorption onto the nonwoven fabric was calculated as previously described. 19 Response surface methodology and statistical analyses…”
Section: Determination Of Adbac Depletion From Solutions Onto Nonwovementioning
confidence: 99%